Prevalence of tonsillar human papillomavirus infection in low-risk individuals without cancer - Jéssica Boscariol da Silva; Aline Oliveira Silva; Luciana Reis Rosa Sacoman; Leandro Luongo Matos; Ronaldo Frizzarini; Raquel Ajub Moyses; José Eduardo Levi (Einstein (São Paulo))
ABSTRACT Objective This study aimed to determine the prevalence of human papillomavirus (HPV) 16 infection in the tonsils of patients without cancer and to analyze the associated risk factors in a low-risk population in Brazil. Methods The study included 113 adult patients who underwent surgery for non-neoplastic conditions. The participants completed an interview-based questionnaire on lifestyle habits, including the use of tobacco and alcohol, and a questionnaire on sexual behavior. Overall, 226 freshly frozen tonsil samples were subjected to DNA extraction, conventional polymerase chain reaction using the PGMY09/11 primer for β-globin, and quantitative polymerase chain reaction for HPV16 detection. Results In this cohort, 47 patients (41.6%) were women between 18 and 58 years of age (mean age, 28.5 years), and 66 (58.4%) were men between 18 and 68 years of age (mean age, 34 years). A total of 81 (71.7%) and 46 (40.7%) patients answered questionnaires on lifestyle habits and sexual behavior, respectively. All samples successfully amplified the β-globin gene fragment but tested negative for HPV DNA. This outcome precluded an investigation of the association between risk factors such as sexual behavior and HPV infection. External validation using oropharyngeal squamous cell carcinoma specimens confirmed the reliability of the laboratory procedures to detect HPV DNA, showing a 10% prevalence of HPV infection in the comparator population. Conclusion The findings of this study suggest that the actual prevalence of HPV16 tonsillar infection in the general population without cancer may be lower than that previously reported in Brazil.